Dr Oen Boen Ing; Patriot doctor, social activist, and doctor of the poor - Lie, Ravando (UI Scholars Hub, 2017)
This article examines the efforts and achievements of Oen Boen Ing, a Tionghoa doctor, to improve the quality of health of the poorer inhabitants of Surakarta. Dr Oen played an important role in five different periods: Dutch colonialism, the Japanese occupation, the Indonesian revolution, Soekarno's regime, and Suharto's New Order. Known for being a benevolent doctor, activist, and patriot of the revolution during his life-time, Dr Oen also gave medical assistance to the needy, which famously earned him the accolade of